Current Meningococcal Vaccines: Advantages and Disadvantages and New Challenges - N. N. Kostyukova; V. A. Bekhalo (Эпидемиология и вакцинопрофилактика, 2016)
The article reviews and analyses the vaccines against invasive meningococcal disease, widely used in practice since 70s-80s of the last century, as well as newly developed ones, the efficacy of which is not completely clear yet. The advantages and disadvantages of polysaccharide and glycoprotein vaccines against meningococci of serogroups A, C, Y, W135 and of protein «vesicle» and geneticengineering vaccines based on «reverse vaccinology» against serogroup B are discussed. Some options for composition of future vaccines under development are presented. Briefly the meningococcal vaccines used in Russia are described. Among the most important immediate tasks discussed are: the study of the duration and intensity of protection after immunization with conjugate vaccines; the development and subsequent trials of a vaccine against serogroup X; further study and improvement of vaccines against serogroup B, as well as the creation of a single vaccine product that protects against all antigenic variants of Neisseria meningitidis.